Modifications in Coagulation Parameters Induced by Treatment Associating Urokinase (2000 u CTA/kg/h) with Heparin - Juhan, I; Calas, M F; Buonocore, M; Mathieu, P; Isnard, G; Cazenave, B; Serradimigni, A (Thrombosis and Haemostasis, 1979)
Twenty-nine patients with deep venous thrombosis of the lower limbs were treated for 48 hours by intravenous infusion of urokinase (2000 u CTA/kg/h) and heparin (5 mg/kg/24 h).Plasma coagulation parameters were measured every 12 hours. After 36 hours of therapy the following results were obtained – decrease in: fibrinogen levels (9% fall), plasminogen (40% decrease), α2-macroglobulin (9% decrease, but no change during the first 12 hours) and fast acting α2-antiplasmin (60% decrease); bidimensional electrophoresis consistently revealed 2 spikes during treatment: the first corresponded to complexed plasmin-fast acting α2-antiplasmin, the second corresponded to free, unconsumed fast acting α2-antiplasmin. Levels of α1-antitrypsin increased by 20% whereas the antithrombin III level remained stable. FDP levels increased slightly. Recalcified plasma coagulation times progressively increased.Therapeutic results were evaluated on phlebography and showed, after 48 hours urokinase administration, improvement in 6 patients and no improvement in 17 cases. Consumption of plasminogen and production of FDP were both greater in the improved patient group.The authors discuss these results and suggest that the dosage level of urokinase used in this study should be modified; it is concluded that a therapeutic regimen associating a loading dose with higher hourly administration levels is needed to achieve neutralization of fast acting α2-antiplasmin, a prerequisite to development of thrombolytic activity.